Community acceptability of use of rapid diagnostic tests for malaria by community health workers in Uganda. - Mukanga, David; Tibenderana, James K; Kiguli, Juliet; Pariyo, George W; Waiswa, Peter; Bajunirwe, Francis; Mutamba, Brian; Counihan, Helen; Ojiambo, Godfrey; Kallander, Karin (BioMed Central Ltd., 2010)
Background: Many malarious countries plan to introduce artemisinin combination therapy (ACT) at community level using community health workers (CHWs) for treatment of uncomplicated malaria. Use of ACT with reliance on presumptive diagnosis may lead to excessive use, increased costs and rise of drug resistance. Use of rapid diagnostic tests (RDTs) could address these challenges but only if the communities will accept their use by CHWs. This study assessed community acceptability of the use of RDTs by Ugandan CHWs, locally referred to as community medicine distributors (CMDs). Methods: The study was conducted in Iganga district using 10 focus group discussions (FGDs) with CMDs and caregivers of children under five years, and 10 key informant interviews (KIIs) with health workers and community leaders. Pre-designed FGD and KII guides were used to collect data. Manifest content analysis was used to explore issues of trust and confidence in CMDs, stigma associated with drawing blood from children, community willingness for CMDs to use RDTs, and challenges anticipated to be faced by the CMDs. Results: CMDs are trusted by their communities because of their commitment to voluntary service, access, and the perceived effectiveness of anti-malarial drugs they provide. Some community members expressed fear that the blood collected could be used for HIV testing, the procedure could infect children with HIV, and the blood samples could be used for witchcraft. Education level of CMDs is important in their acceptability by the community, who welcome the use of RDTs given that the CMDs are trained and supported. Anticipated challenges for CMDs included transport for patient follow-up and picking supplies, adults demanding to be tested, and caregivers insisting their children be treated instead of being referred. Conclusion: Use of RDTs by CMDs is likely to be acceptable by community members given that CMDs are properly trained, and receive regular technical supervision and logistical support. A well-designed behaviour change communication strategy is needed to address the anticipated programmatic challenges as well as community fears and stigma about drawing blood. Level of formal education may have to be a criterion for CMD selection into programmes deploying RDTs.
Community acceptability of use of rapid diagnostic tests for malaria.
Keywords: Community acceptability,f rapid diagnostic tests ,malaria,community health workers,Uganda